Motivasi Bersekolah Jamaah An-Nadzir - Abdurrahman, M. Ali; Widyastuti, Widyastuti (Universitas Negeri Makassar, 2024)
The purpose of this research is to find out the school motivation & the impact of education on An-Nadzir congregants who are pursuing undergraduate education. This research uses a qualitative method with a case study approach. The informants in this study were four people with two main respondents and two significant others. Research data collection was carried out on respondents through interview & documentation techniques. The results obtained by the researcher are that both respondents went to school because of external motivation, namely to prevent the parental restriction on them from believing in An-Nadzir Islam and participating in religious activities in the village. The education made the respondents experience the inner conflict of two opposing identities, namely the identity of Jamaah An-Nadzir and the identity of Educated Individuals. One respondent experienced a belief shifting that made him a Jamaah Bebas Individual. Both respondents became volunteer teachers at An-Nadzir schools as a new way of expressing An-Nadzir's Islamic beliefs. Through this role, the respondents intend to change the congregant’s textual views on islam and make them aware of the importance of education. The implication of this research is that pursuing education up to the undergraduate level can change An-Nadzir's Islamic beliefs.